Saft processing for manually acquired ultrasonic measurement data with 3d smartinspect - Krieg, F.; Kirchhof, J.; Kodera, S.; Lugin, S.; Ihlow, A.; Schwender, T.; Galdo, G. Del; Römer, F.; Osman, A. (Insight, 2019)
The architecture and implementation of a system for synthetic aperture focusing technique (SAFT) reconstruction on ultrasonic data acquired using a hand-held device is described. The reconstruction and the measurement process are performed simultaneously, with the goal of providing instantaneous highly focused visual feedback to the engineer. The implementation is based on the 3D smartInspect system that is currently being developed at Fraunhofer Institute for Nondestructive Testing IZFP. This system assists engineers by recording, displaying and protocolling manually acquired data. In this paper, it is shown that it is possible to enhance this system by adding simultaneous SAFT processing on top of the existing functionality. This improves the imaging quality of the system. Possible limitations on the imaging quality are investigated by real-world hardware set-ups using numerical studies.
CRIS-Team Scopus Importer:2025-11-10
Keywords: 3d smartinspect; Manual inspection procedures; Online processing; Reconstruction; Saft; Ultrasonic inspection